Follow-up study of 6.5 years of admissions to a UK female medium secure forensic psychiatry unit. (27th September 2018) - Tully, John; Cappai, Alessandra; Lally, John; Fotiadou, Maria
Abstract : Aims and method: We aimed to examine clinical and risk outcomes at follow-up, and reoffending and readmission rates, for a sample of 50 admissions to a female medium secure unit (MSU). Demographic, clinical risk assessment (HCR-20 and HoNOS-Secure) and quality of life data were collected using validated measures for all admissions to a female MSU ward in London, UK, between April 2008 and November 2014. Results: All clinical and risk assessment scale scores had improved at follow-up. Quality of life compared favourably to community samples and was good for physical, social and environmental factors and acceptable for psychological health. Twenty-six per cent had at least one readmission, while 17.5% reoffended in the period studied. A longer duration of admission and use of restrictions on discharge was associated with reduced reoffending, but not readmission. Clinical implications: Admission is associated with improvement on clinical risk assessment at follow-up. Longer hospital admissions and use of restrictions on discharge may be necessary to prevent reoffending in this group. Declaration of interest: None.